2004
DOI: 10.1053/j.gastro.2003.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoids, ornithine decarboxylase, and polyamines in primary chemoprevention of familial adenomatous polyposis

Abstract: Background & Aims-Familial adenomatous polyposis because of germline mutation of the adenomatous polyposis coli gene is characterized by development of colorectal adenomas and, ultimately, colorectal cancer. The usefulness of colorectal mucosal compounds to predict the effect on adenoma development of primary chemoprevention with the nonsteroidal anti-inflammatory drug sulindac was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 33 publications
1
82
0
3
Order By: Relevance
“…The APC Min mouse, because of a germ-line mutation in the APC tumor suppression gene, exhibits a high incidence of intestinal adenomas resembling clinical early-onset FAP syndrome (9,10). In recent years, the APC Min model has provided important mechanistic leads for the preventive efficacy of several classes of synthetic pharmacological agents, including non-streroidal anti-inflammatory drugs (NSAIDs), selective enzyme inhibitors, growth factor receptor antagonists and small molecule inhibitors (29,32,(42)(43)(44)(45)(46)(47)(48)(49). These observations have demonstrated a direct correlation between the modulation of pathogenesis and the relevant molecular target for efficacy.…”
Section: Modulation Of Carcinogenesismentioning
confidence: 99%
“…The APC Min mouse, because of a germ-line mutation in the APC tumor suppression gene, exhibits a high incidence of intestinal adenomas resembling clinical early-onset FAP syndrome (9,10). In recent years, the APC Min model has provided important mechanistic leads for the preventive efficacy of several classes of synthetic pharmacological agents, including non-streroidal anti-inflammatory drugs (NSAIDs), selective enzyme inhibitors, growth factor receptor antagonists and small molecule inhibitors (29,32,(42)(43)(44)(45)(46)(47)(48)(49). These observations have demonstrated a direct correlation between the modulation of pathogenesis and the relevant molecular target for efficacy.…”
Section: Modulation Of Carcinogenesismentioning
confidence: 99%
“…However, these interventional strategies are associated with adverse toxic side effects that compromise patient compliance (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, minimally toxic natural dietary components may also modulate the efficacy of toxic chemotherapeutic drugs (35). On the mechanistic level, DFMO functions as a selective inhibitor of ornithine decarboxylase which is an established early response gene and a rate limiting enzyme for the biosynthesis of polyamines (30,31), SUL is a non-selective cyclooxygenase inhibitor (34), EGCG is demonstrated to affect EGF signaling (36), while EPA functions as an inhibitor of lipoxygenase, a critical enzyme for production of leukotrienes (33). All of these targets are known to play important roles in colon carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sulindac inhibits colorectal carcinogenesis in rodent models (9,10) and causes regression of adenomas (2,11) in patients with familial adenomatous polyposis coli. The mechanism by which this activity occurs is unclear, although some correlation has been found between sulindac treatment and reduced levels of prostaglandins in the human colorectal mucosa (12,13). In relation to reduced prostaglandin levels, sulindac treatment was not found to be chemopreventive in all studies (2,13).…”
Section: Introductionmentioning
confidence: 98%
“…The mechanism by which this activity occurs is unclear, although some correlation has been found between sulindac treatment and reduced levels of prostaglandins in the human colorectal mucosa (12,13). In relation to reduced prostaglandin levels, sulindac treatment was not found to be chemopreventive in all studies (2,13). In addition, several studies indicate that sulindac and its metabolites have demonstrated chemoprotective effects through inhibition of angiogenesis (14,15).…”
Section: Introductionmentioning
confidence: 99%